Aspartic protease nepenthesin-1 as a tool for digestion in hydrogen/deuterium exchange mass spectrometry - Kadek, Alan; Mrazek, Hynek; Halada, Petr; Rey, Martial; Schriemer, David C; Man, Petr (Analytical chemistry, 2014)
Hydrogen/deuterium exchange coupled to mass spectrometry (HXMS) utilizes enzymatic digestion of proteins to localize the information about altered exchange patterns in protein structure. The ability of the protease to produce small peptides and overlapping fragments and provide sufficient coverage of the protein sequence is essential for localizing regions of interest. Recently, it was shown that there is an interesting group of proteolytic enzymes from carnivorous pitcher plants of the genus Nepenthes. In this report, we describe successful immobilization and the use of one of these enzymes, nepenthesin-1, in HXMS workflow. In contrast to pepsin, it has different cleavage specificities, and despite its high inherent susceptibility to reducing and denaturing agents, it is very stable upon immobilization and withstands even high concentration of guanidine hydrochloride and reducing agents. We show that denaturing agents can alter digestion by reducing protease activity and/or substrate solubility, and additionally, they influence the trapping of proteolytic peptides onto the reversed phase resin.
Keywords: deuterium; Deuterium; aspartátové proteasy; Hydrogen; vodík; tandemová hmotnostní spektrometrie; Aspartic Acid Proteases; Chromatography, Liquid; chromatografie kapalinová; Tandem Mass Spectrometry